Effects of Liquidity and Solvency on Profitability of PT. State Gas Company (Persero) Tbk - Emi Amelia; Christianingrum Christianingrum; Ratih Hurriyati (Jurnal Inovasi Bisnis dan Kewirausahaan, 2023)
This study examines the effect of liquidity and solvency ratios on profitability. This study used quantitative research. The data of financial reports for the 2016-2021 period was analyzed. This study used multiple linear regression to analyze the data. The test results show that liquidity and solvency positively and significantly affect profitability. The hypothesis testing used the coefficient of determination test (R2), Simultaneous Test (F), and partial test (t) calculating with the SPSS program. The results showed that the liquidity variable partially affected profitability, and the solvency variable had no significant effect on profitability. On the other hand, the Liquidity and Solvency variables simultaneously positively and significantly affected profitability at PT. State Gas Company (Persero) Tbk.